Development of campus ministry program for Columban College, Olongapo City - Presto, Daniel O. (Animo Repository, 1994)
The purpose of this study, to develop a Campus Ministry Program for Columban College, Olongapo City, led to the following specific problems: First, with regards to Program Identification, what are the existing areas and services provided by the Religious Education Program? What are the purposes, goals and objectives, of the program? What are the perceived needs which the program can respond to justify its development? What are the potential returns, potential sources of funding, and linkages that the program can provide? Second, how feasible is the program in terms of physical and technological input, funding and financing, availability of staff, necessary institutional support and level of interest, and considerations of target community? Third, what specific tasks or activities are going to be performed? How are they to be prioritized in terms of work schedule? And fourth, what are the necessary criteria to be followed for program appraisal, selection through a descriptive – development method following a four-phase framework patterned after the Project Management Cycle of Dennis Rondelli. The survey method of descriptive research was used to gather data. There were four sets of questionnaire corresponding to each phase. The items in the questionnaire were pre-tested at Magsaysay Memorial College, San Narciso, Zambales, a sister school of Columban College, to establish their reliability and validity. These sets of questionnaire were later administered to the Administration, College Faculty, non-teaching staff, and Third and Fourth Year College students of Columban College. The respondents were asked to rate the extent to which the College has carried out all the items incorporated in the questionnaire, as well as the extent of their desires and expectations on the same items. All the items in the study were statistically treated using the correlations and Stepwise Regression. The results of the study show that the Religious Education Program is performing on a limited and Moderate extent which means Below Average and Average ratings. The respondents manifested their High Desire for an improved Religious Education Program through the development of Campus Ministry Program for Columban College.